Electronic Fraud and Financial Performance of Deposit Money Banks in Nigeria - Jolaiya, Olatubosun Felix (Business, Management and Economics: Research Progress Vol. 8, 2024)
The study investigated electronic fraud and the financial performance of deposit money banks in Nigeria. The specific objectives were to investigate electronic fraud and banks' financial performance through online web transactions, evaluate the effect of electronic fraud through automated teller machines, determine the effect of fraud through point-of-sale machines, and investigate the effect of fraud through mobile phone USSD transactions on the financial performance of selected deposit money banks in Nigeria. Panel Generalized method of moments (GMM) was used to analyze the panel series of the model. The Hausman test indicated the random effect model as the best fit for the estimation. The major findings of the study revealed that fraud through the automated teller machine (AEF) has a significant negative impact on the financial performance of the deposit money banks in Nigeria. The panel regression result also revealed that fraud through the mobile phone channel (MPEF), and fraud through the online banking channel (OBEF) had a significant negative effect on the financial performance of the banks studied. The study concluded that electronic fraud has a significant negative relationship with the performance of banks. The policy implication of these findings holds for both the management of banks and the financial sector authorities to engineer strategic fraud mitigation technology to strengthen confidence in the financial system. Based on the findings, the study recommended that there is an urgent need for effective monitoring of bank fraud which will allow for the growth of Nigeria's deposit banks' financial performance. This is necessary, especially in this period when the world is going cashless and e-payment instruments are used for cashless banking systems. And failure to do that will affect customer’s confidence in the industry. It is also recommended that Bank fraud shall be reduced through effective supervision and regulation of banks by the monetary authorities so that financial industry will contribute to the economy.